Caracterização de fios supercondutores comerciais de NbTi - Neto, Antônio Barbosa de Lima (Universidade Federal de São Carlos, 2023)
Since the discovery of superconductivity in 1911, various efforts have been employed in the development of superconducting materials. NbTi alloys play an important role in the production of superconducting wires, crucial components for numerous technological applications. The NbTi composition with 46.5% titanium exhibits the most favorable properties, featuring a critical temperature (Tc) of 9 K and a critical magnetic field (Hc) of 14.5 T, both heavily influenced by the material's chemical composition. Conversely, the critical current density (Jc) predominantly depends on the microstructure, derived from processing stages. In this study, superconducting wires from three manufacturers were characterized concerning microstructural aspects and superconducting properties. Through optical microscopy (OM) and scanning electron microscopy (SEM), coupled with energy-dispersive spectroscopy (EDS), it was found that the wires possess a similar chemical composition but exhibit significant structural differences in filament size and distribution. Micrographs revealed analogous microstructures, with deformed α-Ti precipitates in an β-NbTi matrix. Superconducting analyses were obtained using a Physical Property Measurement System (PPMS) coupled with a Vibrating Sample Magnetometer (VMS). Results indicated close critical temperatures (Tc) (between from 9.10 and 9.35 K) and low critical magnetic fields (Hc1) for all three wires (between 0.045 and 0.3 T). Due to equipment limitations, the upper critical magnetic field (Hc2) was determined using the Kramer method, yielding results between 14 and 17 T. Critical current density was indirectly obtained from the magnetization curve, with values ranging from 4.84x107 to 6.00x108 A/m². In conclusion, the observed variations in wire properties among the wires can likely be attributed to geometric and/or microstructural factors, as the chemical compositions remain similar.
Characterization of commercial NbTi superconducting wires
Keywords: Supercondutividade; NbTi; Corrente crítica; Temperatura crítica; Campo magnético crítico; Aprisionamento de fluxo; Superconductivity; Critical current; Critical temperature; Critical magnetic field; Flux pinning; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::SUPERCONDUTIVIDADE